Effectiveness of Complete Systematic Land Registration (PTSL) Services in the Sinjai District Land Office - M. Erwin Syukri; Andi Dea Nanda Sapira; Abdul Ganie Gaffar; Muhammad Suyuti (Journal of Social and Humanities, 2024)
The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency has implemented the Acceleration of Complete Systematic Land Registration (PTSL) policy to reduce disputes and ensure legal certainty for land owners. This research aims to evaluate the effectiveness of PTSL services carried out by the Sinjai Regency Land Office. This research use desciptive qualitative approach. The data collection procedure involved observation, interviews, and documentation, with research subjects involving the Chair of the PTSL Adjudication Committee, Deputy Chair of the PTSL Jurisdiction Division, and program beneficiaries in Sinjai Regency. The research results show that PTSL services in Sinjai Regency have proven to be effective in terms of understanding the program, being on target and achieving goals. Even though there is an understanding of duties and responsibilities, as well as public awareness of the objectives and stages of PTSL, there are still obstacles in meeting indicators on time. Although most of the program targets have been achieved, some targets remain unfulfilled. The indicators for achieving the program objectives are quite effective, this is because the implementation of the PTSL program in Sinjai Regency is in accordance with the objectives of the PTSL program, namely that all land plots in the territory of the Republic of Indonesia have been mapped, but have not yet been mapped and are able to achieve the specified targets. Indicators of real change are effective because with the PTSL program, people can have ownership certificates in an easy and fast process.